Perturbation of energy metabolism by fatty-acid derivative AIC-47 and imatinib in BCR-ABL-harboring leukemic cells. Issue 1 (1st February 2016) - Shinohara, Haruka; Kumazaki, Minami; Minami, Yosuke; Ito, Yuko; Sugito, Nobuhiko; Kuranaga, Yuki; Taniguchi, Kohei; Yamada, Nami; Otsuki, Yoshinori; Naoe, Tomoki; Akao, Yukihiro
Highlights: Imatinib strongly suppresses Warburg effect through the down-regulation of PTBP1. Fatty-acid oxidation (FAO) supports glucose-independent survival in imatinib-treated cells. Inactivation of BCR-ABL activates compensatory FAO. AIC-47 perturbs both glycolysis and FAO. The inhibition of glycolysis and FAO can be effective for the CD34 + fraction. Abstract: In Ph-positive leukemia, imatinib brought marked clinical improvement; however, further improvement is needed to prevent relapse. Cancer cells efficiently use limited energy sources, and drugs targeting cellular metabolism improve the efficacy of therapy. In this study, we characterized the effects of novel anti-cancer fatty-acid derivative AIC-47 and imatinib, focusing on cancer-specific energy metabolism in chronic myeloid leukemia cells. AIC-47 and imatinib in combination exhibited a significant synergic cytotoxicity. Imatinib inhibited only the phosphorylation of BCR-ABL; whereas AIC-47 suppressed the expression of the protein itself. Both AIC-47 and imatinib modulated the expression of pyruvate kinase M (PKM) isoforms from PKM2 to PKM1 through the down-regulation of polypyrimidine tract-binding protein 1 (PTBP1). PTBP1 functions as alternative splicing repressor of PKM1, resulting in expression of PKM2, which is an inactive form of pyruvate kinase for the last step of glycolysis. Although inactivation of BCR-ABL by imatinib strongly suppressed glycolysis, compensatory fatty-acid oxidation (FAO) activation supported glucose-independent cell survival by up-regulating CPT1C, the rate-limiting FAO enzyme. In contrast, AIC-47 inhibited the expression of CPT1C and directly fatty-acid metabolism. These findings were also observed in the CD34 + fraction of Ph-positive acute lymphoblastic leukemia cells. These results suggest that AIC-47 in combination with imatinib strengthened the attack on cancer energy metabolism, in terms of both glycolysis and compensatory activation of FAO.